A novel and fully validated hydrophilic interaction liquid chromatography with tandem mass spectrometry method for the determination of intact carboplatin in human plasma. Issue 4 (25th March 2018) - Ren, Guanghui; Qin, Zhiying; Fan, Ali; Wang, Yonghan; Tan, Yanan; Lu, Yang; Li, Ning; Chen, Xijng; Zhao, Di
Abstract: Carboplatin is an anticancer drug widely used to treat a variety of cancers. However, a simple, sensitive and rapid method for the quantitation of intact carboplatin is still absence for therapeutic drug monitoring or clinical trials. In this work, a rapid, universal, and reliable hydrophilic interaction liquid chromatography with tandem mass spectrometry method for the determination of intact carboplatin in human plasma was developed and fully validated. Carboplatin was extracted from human plasma by simple protein precipitation with acetonitrile. A good chromatographic separation of carboplatin was achieved on a Waters XBridge HILIC column (2.1 × 150 mm, 3.5 μm), with the analytical time 5.5 min for one sample. The linearity range of the assay was from 10 to 2000 ng/mL. The method was linear ( r 2  > 0.9989), accurate (<6% bias, 12% bias at LOQ) and precise (intra‐day and inter‐day precision of <3% coefficient of variation). The stability of intact carboplatin in human plasma with three different anticoagulants was assessed in this study. Furthermore, the matrix effect of hemolysis and hyperlipidemic samples was also evaluated for the first time. This work made the routine determination of intact carboplatin feasible and universal in clinical practice.